Centrosomes, chromosome instability (CIN) and aneuploidy - Vitre, Benjamin D. (2012)
Each time a cell divides its chromosome content must be equally segregated into the two daughter cells. This critical process is mediated by a complex microtubule based apparatus, the mitotic spindle. In most animal cells the centrosomes contribute to the formation and the proper function of the mitotic spindle by anchoring and nucleating microtubules and by establishing its functional bipolar organization. Aberrant expression of proteins involved in centrosome biogenesis can drive centrosome dysfunction or abnormal centrosome number, leading ultimately to improper mitotic spindle formation and chromosome missegregation. Here we review recent work focusing on the importance of the centrosome for mitotic spindle formation and the relation between the centrosome status and the mechanisms controlling faithful chromosome inheritance.